Socioeconomic Geography of Offshore Finance in Mexico - Tovar-Cabañas, Rodrigo; Márquez-Roa, Ubaldo; Herrera-Meza, Grecia (FLACSO - Sede Ecuador, 2023)
This paper explores the information contained in the Panama papers, whose relevance continues to be present since the revelation in 2016. The objective is to characterize the territorial structure of the main international financial flows that passed through Mexico, Through socio-spatial networks analysis, the universe of study was limited to a thousand revelations. With the help of the logical tools of the Gephi software, it was possible to visualize the point clouds of the structure of offshore finance in Mexico. The study reveals that 36% of tax havens or offshore are carried out in the Miguel Hidalgo mayor's office of Mexico City, 8.8% correspond to the municipality of San Pedro Garza García, Nuevo León, while 5.3% correspond to the Cuajimalpa de Morelos mayor's office in Mexico City. Finally, it was possible to locate the main tax havens with which the offshore finance network of Mexico interacts.